OP88 Advance care planning and spousal couples affected by dementia: a constructivist grounded theory. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Ryan, T; McKeown, J
Abstract : Background: Global policy and clinical guidelines place emphasis on the implementation and use of advance care planning (ACP) to inform decision making about care and treatment at the end of life. For people with dementia, where its use is encouraged at the point of diagnosis, utilisation of ACP is relatively low, raising concerns about the challenges present in the context of the condition. This study explores the ways in which co-residing couples considered ACP in the light of a recent diagnosis of dementia. Method: Using face-to-face interviews as part of a constructivist grounded theory methodology the study sought to understand how people with dementia and their long-term co-residing partners consider and plan, or do not plan, for future medical and social care. Results: Sixteen participants were interviewed. They identified the importance of relationships in the process of planning alongside an absence of formal service support. As a result few engaged in ACP. Findings recognise the fundamental challenges faced by couples when considering end-of-life decisions whilst making efforts to 'live well'. Importantly, the paper identifies features of the ACP experience of a relational and biographical nature. Conclusion: The study challenges the relevance of current global policy and practice, concluding that what is evident is a process of 'emergent planning' through which couples build upon their knowledge of dementia, their networks and relationships, and a series of 'tipping points' in the process of considering future care options. The relational and collective nature of future planning is also emphasised.